2019
DOI: 10.1007/s42729-019-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Bokashi as an Amendment and Source of Nitrogen in Sustainable Agricultural Systems: a Review.

Abstract: Integral soil fertility is managed by practices that contribute to organic matter, which improves its properties. Bokashi is an organic amendment that can be part of the tools used in sustainable soil management. This review systematizes existing information regarding the production and use of bokashi. In addition to discussing guidelines for the production and use of good-quality bokashi, it also focuses on the availability of N and microbial aspects, using compost as a reference amendment. Through this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 69 publications
(77 reference statements)
1
29
0
4
Order By: Relevance
“…plantenresten van de landbouw, bermmaaisel en gft-afval (Olle, 2021). Bokashi lijkt veel op compost, het heeft ook een hoog organischestof-en nutriëntengehalte (Quiroz and Céspedes, 2019). Omdat er zoveel verschillende inputmaterialen gebruikt kunnen worden, is bokashi erg verschillend van kwaliteit (Quiroz and Céspedes, 2019).…”
Section: Compost En Bokashiunclassified
See 1 more Smart Citation
“…plantenresten van de landbouw, bermmaaisel en gft-afval (Olle, 2021). Bokashi lijkt veel op compost, het heeft ook een hoog organischestof-en nutriëntengehalte (Quiroz and Céspedes, 2019). Omdat er zoveel verschillende inputmaterialen gebruikt kunnen worden, is bokashi erg verschillend van kwaliteit (Quiroz and Céspedes, 2019).…”
Section: Compost En Bokashiunclassified
“…Bokashi lijkt veel op compost, het heeft ook een hoog organischestof-en nutriëntengehalte (Quiroz and Céspedes, 2019). Omdat er zoveel verschillende inputmaterialen gebruikt kunnen worden, is bokashi erg verschillend van kwaliteit (Quiroz and Céspedes, 2019). Zo heeft bokashi gemaakt van gft-afval bijvoorbeeld een hoger gehalte aan nutriënten dan bokashi gemaakt van bermmaaisel (Romkens et al, 2020).…”
Section: Compost En Bokashiunclassified
“…Bokashi, meaning 'fermented organic matter', derives from traditional Japanese composting methods that involve the mixing of food waste with soils, with the key ingredient being 'efficient microorganisms' (yeasts and bacteria) which aid fermentation and the production of rich soil nutrients. Research has shown that in many cases bokashi manure can produce the same increases in soil fertility and crop production as artificial fertilisers (Xiaohou et al 2008;Quiroz and Cespedes, 2019). Because it uses local waste products found in and around the farm (crop residues, animal manure, ash, maize bran) bokashi manure is both environmentally friendly and low-cost.…”
Section: The Deep-bed Farming Systemmentioning
confidence: 99%
“…However, for arugula (Eruca sativa L.) and radish (Raphanus sativus L.), higher yields have been achieved with 10% and 5% BM, respectively [2]. Effective microorganism (EM) Bokashi is a well-known soil amendment used in agriculture [3,4], and has been tested with promising results for tomato [5,6], arugula [2], radish [2], and lettuce (Lactuca sativa L.) [7]. Based on 130 long-term experiments, organic amendments provided stability in plant and fruit production, and may increase yield by up to 15% in tropical conditions [8].…”
Section: Introductionmentioning
confidence: 99%